Microsoft Office 97 : integration (ViaGrafix OklahomaUS, 1999)
Presentation describes how information and data can be shared and combined between the various Microsoft Office products - Word, Excel, Powerpoint, Access and Outlook.
Includes diskette with files which can be copied onto the hard drive and used for hands-on exercises with the specified application.